Takayasu Arteritis - Russo, Ricardo A. G. (Front Pediatr, 2018)
Takayasu arteritis is an idiopathic granulomatous vasculitis of the aorta and its main branches and it constitutes one of the more common vasculitides in children. Inflammation and intimal proliferation lead to wall thickening, stenotic or occlusive lesions, and thrombosis, while destruction of the elastica and muscularis layers originates aneurysms and dissection. Carotid artery tenderness, claudication, ocular disturbances, central nervous system abnormalities, and weakening of pulses are the most frequent clinical features. The diagnosis is usually confirmed by the observation of large vessel wall abnormalities: stenosis, aneurysms, occlusion, and evidence of increased collateral circulation in angiography, MRA or CTA imaging. The purpose of this revision is to address the current knowledge on pathogenesis, investigations, classification, outcome measures and management, and to emphasize the need for timely diagnosis, effective therapeutic intervention, and close monitoring of this severe condition.